2018
DOI: 10.1680/jgein.17.00035
|View full text |Cite
|
Sign up to set email alerts
|

Durability of reinforced PVC-P geomembranes installed in reservoirs in eastern Spain

Abstract: The aim of this paper is to study the durability of polyvinyl chloride (PVC-P) geomembranes reinforced with a synthetic fabric in hydraulic works in the Spanish Mediterranean basin. Therefore, a set of six geomembranes installed in irrigation reservoirs for 18-31 years were analysed. The initial characteristics of the geomembranes were determined to verify fulfilment of the Spanish regulations in force at the time. The characteristics were then assessed, and the results were interpreted with reference to the l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 10 publications
(11 reference statements)
1
1
0
2
Order By: Relevance
“…In addition, there is a tendency for tensile strength to increase with age, as the membrane loses flexibility over time. 9 Similar observations were made in a study by Blanco et al 10 , where both load and tensile strength in longitudinal and transversal directions were evaluated for 35-year-old geomembranes with reinforced polyester.…”
Section: Mechanical Performancesupporting
confidence: 67%
See 1 more Smart Citation
“…In addition, there is a tendency for tensile strength to increase with age, as the membrane loses flexibility over time. 9 Similar observations were made in a study by Blanco et al 10 , where both load and tensile strength in longitudinal and transversal directions were evaluated for 35-year-old geomembranes with reinforced polyester.…”
Section: Mechanical Performancesupporting
confidence: 67%
“…They confirmed reduced low-temperature flexibility and elongation at break points following plasticizer migration. Blanco et al 10 investigated the long-term behaviour of high-density polyethylene (HDPE), ethylene-propylene-diene monomer (EPDM) and plasticized PVC membranes, and reported that the shear strength of Kravanja et al: Degradation of Plasticized Poly(1-chloroethylene) ... joints remained relatively unaffected by ageing despite the loss of plasticiser. Kositchaiyong et al 11 studied anti-fungal performance and mechanical-morphological properties of PVC and wood/PVC composites under the influence of soil and UV light, and concluded that UV weathering reduced the antifungal performance of the material from 81.4% to 28.3%.…”
Section: Introductionmentioning
confidence: 99%
“…However, for textured geomembranes, which have raised areas on one or both sides to enhance friction with adjacent layers, the thickness cannot be defined as a single value. Instead, the core thickness and the heights of the raised areas (asperities) need to be measured separately [39].…”
Section: Introductionmentioning
confidence: 99%
“…Alrededor de 1940 se empezaron a utilizar láminas de PVC plastificado (PVC-P) y otros polímeros como elemento impermeable en la construcción y renovación de obras hidráulicas [2]. Desde entonces el uso de dichos materiales, conocidos en la actualidad como geomembranas, se ha perfeccionado y tecnificado hasta convertirse en un elemento fundamental en las obras hidráulicas modernas, con infinidad de casos de éxito en los que las láminas llevan décadas en uso con un perfecto funcionamiento [3][4][5].…”
Section: Geomembranas Para Impermeabilización De Balsas: Cómo Y Por Qué Se Degradanunclassified
“…La degradación de las geomembranas utilizadas en la impermeabilización de balsas es un proceso que, si se trata de productos adecuadamente formulados, tiene lugar durante décadas hasta que el producto alcanza el final de su vida útil. Existe abundante bibliografía que recoge casos de éxito en los que las geomembranas han estado (o siguen estando) en uso después de 40 años [3][4][5].…”
Section: Envejecimiento Acelerado En Laboratoriounclassified